PENGARUH KUALITAS PELAYANAN DAN TINGKAT KEPERCAYAAN TERHADAP KEPUASAAN NASABAH PADA PT BCA FINANCE KANTOR PUSAT PONDOK INDAH JAKARTA SELATAN - Caroline, Ruth Jesica; Simarmata, P.; Murtatik, Sri (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
This study was conducted to examine the effect of variable Quality of Service and Customer Satisfaction Level of Confidence in PT BCA Finance. The population in this study are customers of PT BCA Finance in BCA Wisma Pondok Indah, South Jakarta. In determining the sample size formula used is roscoe formula because the population is not known with certainty and the sample was 100 respondents. The sampling technique used was purposive sampling. The type of data used are primary data, data sources obtained from questionnaires, and collection of data from this study of the questionnaire that was distributed. Technical analysis used is multiple linear regression and hypothesis testing using t test and F test with confidence level is 5%. Results of this study is to show that all influential variables simultaneously and partially towards customer satisfaction.